2014
DOI: 10.1108/oir-10-2013-0240
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of online corporate reporting in three Latin American markets

Abstract: Purpose -The purpose of this paper is to explore the determinants of online corporate reporting in three Latin American emerging markets, Argentina, Mexico and Chile, providing further evidence to test the mediation role of web presence development in the relationship between these determinants and e-disclosure. Web presence development measures the firm's efforts to archive web visibility, web usability and convenience. Design/methodology/approach -Based on a content analysis of corporate web sites, the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 67 publications
2
26
0
8
Order By: Relevance
“…On the other hand, Bollen, Hassink and Bozic (2006) and Boubaker, Lakhal and Nekhili (2012) found significant associations between online IR quality and the IT industry, whilst Bonson and Escobar (2006) and Dolinšek, Tominc and Skerbinjek (2014) reported that the financial services industry was a significant predictor. Other studies found no industry association with online IR (Desoky, 2009;Uyar, 2012;Fuertes-Callén, Cuellar-Fernández, & Pelayo-Velázquez, 2014). Internationally, it seems the literature is inconclusive as to whether natural resource companies would be associated with higher online IR.…”
Section: Literature Review and Hypothesismentioning
confidence: 98%
“…On the other hand, Bollen, Hassink and Bozic (2006) and Boubaker, Lakhal and Nekhili (2012) found significant associations between online IR quality and the IT industry, whilst Bonson and Escobar (2006) and Dolinšek, Tominc and Skerbinjek (2014) reported that the financial services industry was a significant predictor. Other studies found no industry association with online IR (Desoky, 2009;Uyar, 2012;Fuertes-Callén, Cuellar-Fernández, & Pelayo-Velázquez, 2014). Internationally, it seems the literature is inconclusive as to whether natural resource companies would be associated with higher online IR.…”
Section: Literature Review and Hypothesismentioning
confidence: 98%
“…9, No. 1 addition, some companies are reluctant to disclose specific types of information such as customers and employees information (e.g., Lodhia et al, 2004), forward-looking information (e.g., Sriram & Laksmana, 2006;Sánchez et al, 2011), products or services quality (e.g., Álvarez, Sanchez & Dominguez, 2008;Fuertes-Callén, Cuellar-Fernández, & Pelayo-Velázquez, 2014), strategic information (e.g., Sánchez et al, 2011) and innovation (e.g., Cormier et al, 2010).…”
Section: Business and Management Horizonsmentioning
confidence: 99%
“…Apesar de a teoria apontar uma associação, diversos estudos não verificaram uma relação significativa entre a divulgação voluntária web-based e maior rentabilidade (Ahmed et al, 2009;Ojah & Mokaleli-Mokoteli, 2012;Juhmani, 2013;Sharma, 2013;Angonese, Sanches, & Bezerra, 2014;Fuertes-Callén et al, 2014).…”
Section: Rentabilidadeunclassified